Clinical outcome and risk factors for failure in late acute prosthetic joint infections treated with debridement and implant retention. Issue 1 (January 2019) - Wouthuyzen-Bakker, Marjan; Sebillotte, Marine; Lomas, Jose; Taylor, Adrian; Palomares, Eva Benavent; Murillo, Oscar; Parvizi, Javad; Shohat, Noam; Reinoso, Javier Cobo; Sánchez, Rosa Escudero; Fernandez-Sampedro, Marta; Senneville, Eric; et al.
Highlights: Late acute prosthetic joint infection (PJI) treated with surgical debridement and implant retention have a high failure rate. The exchange of mobile components during surgical debridement is the most potent predictor for treatment success. There are several preoperative patient related variables that increase the risk for failure. Treatment strategies for late acute PJIs should be individualized and optimized according to the preoperative risk for failing. Summary: Objectives: Debridement, antibiotics and implant retention (DAIR) is the recommended treatment for all acute prosthetic joint infections (PJI), but its efficacy in patients with late acute (LA) PJI is not well described. Methods: Patients diagnosed with LA PJI between 2005 and 2015 were retrospectively evaluated. LA PJI was defined as the development of acute symptoms (≤ 3 weeks) occurring ≥ 3 months after arthroplasty. Failure was defined as: (i) the need for implant removal, (ii) infection related death, (iii) the need for suppressive antibiotic therapy and/or (iv) relapse or reinfection during follow-up. Results: 340 patients from 27 centers were included. The overall failure rate was 45.0% (153/340). Failure was dominated by Staphylococcus aureus PJI (54.7%, 76/139). Significant independent preoperative risk factors for failure according to the multivariate analysis were: fracture as indication for the prosthesis (odds ratio (OR) 5.4), rheumatoid arthritis (OR 5.1), age above 80 years (OR 2.6), male gender (OR 2.0) and C-reactive protein > 150 mg/L (OR 2.0). Exchanging the mobile components during DAIR was the strongest predictor for treatment success (OR 0.35). Conclusion: LA PJIs have a high failure rate. Treatment strategies should be individualized according to patients' age, comorbidity, clinical presentation and microorganism causing the infection.